TECHNICAL EFFICIENCY OF BAMBARA GROUNDNUT PRODUCTION IN NORTHERN GHANA (2015)
Achieving food security under climate change is one of the greatest concerns of governments in developing countries. Due to favourable agronomic characteristics such as drought tolerance and an ability to produce a crop on less fertile soils, a number of under-utilised crops, such as bambara groundnut offer potentials to address food insecurity problems in areas impacted by climate change. While efficiency studies have gained popularity in relation to many food crops, very little research has been carried out on the technical efficiency of bambara groundnut production. This study estimated a Translog stochastic frontier to determine the factors that influenced farmers’ technical efficiency in the 2013 cropping season in Northern Ghana. It involved 120 farmers selected through a multi-stage sampling technique. Technical efficiency scores ranged from 27% to 97% with a mean of 83%. The significant positive determinants of output and efficiency were farm size, household labour, organic fertilisers as well as education and off-farm activities. The study found that bambara groundnut production can be stepped up by supporting farmers to scale up their farms, form farmer groups, diversify their livelihoods and improve the use of organic fertilizers. Improving opportunities for formal education may also have a positive impact.